Payment options: An analysis of 6 years of payment plan data and potential implications for for-profit clinics, non-profit veterinary providers, and funders to access to care initiatives - Cammisa, Heather J.; Hill, Samantha (Frontiers in Veterinary Science, 2022)
Analyzing a dataset of payment plans disassociated with traditional credit scoring, this research, for the first time, offers insights into the mitigation of cash flow and credit ineligibility challenges in access to veterinary care. Specifically, this paper explores financial fragility among pet families and whether payment options offer substantial bridges in access to care challenges for veterinarians and clients. Researchers introduce a veterinary care multiplier to estimate the potential increase in veterinary care that may be provided by for-profit and non-profit clinics from additional payment options. The implications for nonprofits working to address access to care is that by directing donor dollars to cover the 6.9% that is potentially left unpaid in meeting pet families simply facing cash flow challenges, a non-profit clinic could provide 14.5 times the veterinary care versus full subsidies. In for-profit clinics, allocating some of a clinic’s discount budget may similarly yield 14.5 times the care for clients likely to be declined by traditional credit options. Further research is recommended to explore how deeply these options penetrate all financially fragile pet owners as well as outcomes in the absence of these tools for credit declined clients. Additional research to determine the levels at which payment options reduce economic euthanasia decisions, reduce client and staff stress, increase value perception and compliance with suggested care, enable better outcomes for patients and increase clinic revenue is also recommended. The researchers conclude that payment options independent of traditional credit scoring mitigate financial barriers to obtaining veterinary care.